THE LEGAL POLICY OF CITIZENSHIP IN FULFILLING THE RIGHTS OF STATELESS PERSONS AS AN EFFORT TO FULFILL HUMAN RIGHTS IN INDONESIA - Sekar Anggun Gading Pinilih; Aditya Yuli Sulistyawan; Irma Cahyaningtyas; Adya Paramita Prabandari (Fakultas Hukum, Universitas Diponegoro, 2022)
The issue of citizenship is one of the basic human needs, therefore citizenship status is a right for every citizen that is protected by law. The purpose of this study is to find out how the legal politics of Indonesia in the context of stateless person citizenship rights. This research is normative juridical research that uses a statute approach and a conceptual approach. Based on the results of the study, it was found that legal politics in the form of regulations regarding citizenship in Indonesia from time to time was sufficient to guarantee the rights of Indonesian citizens. However, the Indonesian Citizenship Law does not specifically regulate the stateless person. In addition, there is no policy regarding the granting of citizenship status to stateless persons, so many cases of stateless persons in Indonesia are detained by immigration authorities. Thus, the Indonesian government should emphasize its legal policy in order to optimize legal protection for stateless persons in Indonesia.